-5(-8n+4)=18+2n

Simple and best practice solution for -5(-8n+4)=18+2n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(-8n+4)=18+2n equation:



-5(-8n+4)=18+2n
We move all terms to the left:
-5(-8n+4)-(18+2n)=0
We add all the numbers together, and all the variables
-5(-8n+4)-(2n+18)=0
We multiply parentheses
40n-(2n+18)-20=0
We get rid of parentheses
40n-2n-18-20=0
We add all the numbers together, and all the variables
38n-38=0
We move all terms containing n to the left, all other terms to the right
38n=38
n=38/38
n=1

See similar equations:

| 3=-x+2x | | 17x=10x*x+3 | | -2n+-6+-4=8 | | −5(x+2)+2x+5=-2−2 | | -24=7p+5p | | 3n-21=6(-6n+3) | | 9=-4p+p | | 1-k=6k+8 | | 45-4w=w | | 17x=10x+3 | | p-19=-35 | | 75x+25=42x+36 | | 7(a-8)=3(a+4) | | -14+6n-14-18=-4 | | -26=p-17 | | 24+5v=11v | | 3=3+n | | 3x-7+2x=4+5x-11 | | 5(-2x+5)+x-5=-48 | | 13+v=14 | | 3p+6=57 | | 1-2m=-6m-3 | | 8x+14∘=6x+34∘ | | w÷(-4)=-0.9 | | 1-((x-5)/3)=((x+2)/5)-((6x-1)/15) | | 3x-7=2(x+4)+x-1 | | 19-6p=-41 | | 79-(-5x-6)0=245x+336 | | 22-2f=6 | | 3(x+1)=2x+4+x-1 | | 2q-8q+9=-8q-9 | | 4v=-68 |

Equations solver categories